2018
DOI: 10.1111/exd.13701
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of cutaneous lymphomas

Abstract: Primary cutaneous T-cell lymphoma (CTCL) comprises the second most common group of extra-nodal non-Hodgkin's lymphoma. They represent incurable primary extra-nodal lymphomas of major T cells, uniformly present in the skin with 1%-2% risk of systemic dissemination in mycosis fungoides (MF), which represents the most common subtype of CTCL. In general, long-term antigen stimulation is thought, through key cytokine signalling pathways, to induce an inflammatory response with T-cell proliferation, leading to a clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
14
1
1
Order By: Relevance
“…Chronic stimulation leads to the activation of T helper cells, followed by proinflammatory cytokines release and chronic inflammation, that will finally lead to a clonal malignant T-cell with continuous expansion [24,25]. Impaired skin reactivity to antigens was also described from asbestos exposure [26], but, on the present experimental data, we cannot assign it to the MF development. We are aware that a potential relation between cutaneous lympho-proliferative disorders and asbestos needs further epidemiological data gathering which is not an easy task since mycosis fungoides occurs only in 3.6-5.6 per million individuals [27].…”
Section: Alexandra Maria Rașcu Gabriela Neicu Agripina Rașcu Marincontrasting
confidence: 52%
“…Chronic stimulation leads to the activation of T helper cells, followed by proinflammatory cytokines release and chronic inflammation, that will finally lead to a clonal malignant T-cell with continuous expansion [24,25]. Impaired skin reactivity to antigens was also described from asbestos exposure [26], but, on the present experimental data, we cannot assign it to the MF development. We are aware that a potential relation between cutaneous lympho-proliferative disorders and asbestos needs further epidemiological data gathering which is not an easy task since mycosis fungoides occurs only in 3.6-5.6 per million individuals [27].…”
Section: Alexandra Maria Rașcu Gabriela Neicu Agripina Rașcu Marincontrasting
confidence: 52%
“…However, a negative clonality test does not exclude a diagnosis of MF . Newly emerging advanced molecular technology using high throughput TCR sequencing of the CDR3 (complementary determining regions) of TCR‐beta and TCR‐gamma genes, may be helpful in discriminating early MF from other inflammatory dermatoses; however, access to testing is limited. The majority (4/5) of cases in our cohort who had molecular studies performed showed the presence of a neoplastic T‐cell clone by TCR PCR studies.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Diagnostic discordance in early MF has been noted in approximately 20% of cases. 9 This may lead to vague, non-specific and inconclusive pathology interpretations of early stage lesions of MF 28 39 ; however, access to testing is limited. The majority (4/5) of cases in our cohort who had molecular studies performed showed the presence of a neoplastic T-cell clone by TCR PCR studies.…”
Section: Discussionmentioning
confidence: 99%
“…[19] These studies were summarized by R. Stadler and R. Stranzenbach to give a precise view of the current knowledge in the understanding of the molecular pathogenesis of CTCL. [20] These genetic changes lead to T cells that show apoptosis deficits and a consequent continuous expansion. During this process, the malignant cells show increased differentiation into T helper type 2 cells with corresponding cytokine production of interleukin 4 and 13 and resistance to normal cell control mechanisms.…”
Section: Comple X Mutational L Andsc Ape In C Tclmentioning
confidence: 99%